2010
DOI: 10.1007/s12583-010-0093-1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of subaerial karstification and late reconstruction in the Dengying Formation, Sichuan basin, southwestern China

Abstract: Tectonic uplift at the end of Sinian resulted in the denudation of the Dengying (灯影) Formation on a different scale and the development of a great number of secondary dissolution vugs beneath the unconformity between Sinian and Cambrian. Geological and geochemical characteristics such as the development of caves, sinkholes, karst tubes and weathering crust, abrupt depletion and negative deflection of δ 13 C and δ 18 O in country rock and vug filling toward unconformity surface suggest that subaerial karstifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Sedimentological observations suggest that the karstification events of shallow carbonate platforms may be widespread in the late Ediacaran Period. Notably, similar karstification textures of carbonate breccia, aragonite crystal fans and botryoidal aragonites have also been found from other correlative sections, including the other Dengying sections in South China (Zhang, 1980;Cao & Xue, 1983;Siegmund & Erdtmann, 1994;Xiang et al 2001;Wang et al 2010Wang et al , 2012Shi et al 2011;Liu et al 2012;Mo et al 2013;Zhang et al 2014b;Lin et al 2015;Mou et al 2015;Lian et al 2016Lian et al , 2017, the Qigebulake Formation in the Tarim basin in Northwestern China (Qian et al 2017), the Buah Formation in Oman (Gorin et al 1982;Cozzi & Al-Siyabi, 2004;K. D. Bergmann, unpub.…”
Section: G Implications For Early Metazoan Evolutionsupporting
confidence: 55%
See 1 more Smart Citation
“…Sedimentological observations suggest that the karstification events of shallow carbonate platforms may be widespread in the late Ediacaran Period. Notably, similar karstification textures of carbonate breccia, aragonite crystal fans and botryoidal aragonites have also been found from other correlative sections, including the other Dengying sections in South China (Zhang, 1980;Cao & Xue, 1983;Siegmund & Erdtmann, 1994;Xiang et al 2001;Wang et al 2010Wang et al , 2012Shi et al 2011;Liu et al 2012;Mo et al 2013;Zhang et al 2014b;Lin et al 2015;Mou et al 2015;Lian et al 2016Lian et al , 2017, the Qigebulake Formation in the Tarim basin in Northwestern China (Qian et al 2017), the Buah Formation in Oman (Gorin et al 1982;Cozzi & Al-Siyabi, 2004;K. D. Bergmann, unpub.…”
Section: G Implications For Early Metazoan Evolutionsupporting
confidence: 55%
“…In geological records, botryoidal aragonites of both marine origin (Ginsburg & James, 1976;Mazzullo & Cys, 1979;Aissaoui, 1985;Jiang et al 2006a) and non-marine origin (Mazzullo, 1980;Aissaoui, 1985) have been reported. Proposed interpretations for the Dengying aragonites include primary syn-depositional seafloor precipitates (Zhang, 1980;Cao, 2002;Zhang et al 2014b;Lin et al 2015;Peng et al 2017), authigenic carbonates formed in meteoric waters (Wang et al 2010;Shi et al 2011), authigenic carbonates formed in marine environments (Si et al 2014;Hao et al 2015;Mou et al 2015;Tan et al 2015) and late authigenic carbonates formed during burial diagenesis (Wang et al 2000).…”
Section: Terminal Ediacaran Sedimentology and Chemostratigraphymentioning
confidence: 99%